Elementary School Students’ Learning Motivation in Relation to School and Family Environment Conditions - Kamasiah; Karim; Agusalim; Muhammad Yusnan (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
Learning motivation is an important factor that influences students' success in the educational process, especially at the elementary school level. This study aims to determine how the conditions of the school and family environments affect students’ learning motivation. A conducive school environment and positive family support are believed to enhance students’ enthusiasm and willingness to learn. This research employed a quantitative approach using a survey method. Data were collected through a closed-ended questionnaire based on a Likert scale, which was distributed to students in grades IV, V, and VI. The instrument was tested for validity and reliability before being used for data collection. The results of the study show a significant relationship between the conditions of the school and family environments and the level of students’ learning motivation. A safe, clean school environment and harmonious relationships with teachers and peers positively impact students' motivation. Similarly, parental attention in supporting children’s learning at home serves as an essential supporting factor. In conclusion, students’ learning motivation is generally influenced by two main factors: a supportive school environment and a family that provides consistent attention and encouragement.